Outcome reporting in therapeutic mammaplasty: a systematic review. Issue 6 (11th December 2021) - Lee, Alice; Kwasnicki, Richard M; Khan, Hasaan; Grant, Yasmin; Chan, Abigail; Fanshawe, Angela E E; Leff, Daniel R
Abstract: Background: Therapeutic mammaplasty (TM) is an oncological procedure which combines tumour resection with breast reduction and mastopexy techniques. Previous systematic reviews have demonstrated the oncological safety of TM but reporting of critically important outcomes, such as quality of life, aesthetic and functional outcomes, are limited, piecemeal or inconsistent. This systematic review aimed to identify all outcomes reported in clinical studies of TM to facilitate development of a core outcome set. Methods: Medline, EMBASE, CINAHL and Web of Science were searched from inception to 5 August 2020. Included studies reported clinical outcomes following TM for adult women. Two authors screened articles independently for eligibility. Data were extracted regarding the outcome definition and classification type (for example, oncological, quality of life, etc.), time of outcome reporting and measurement tools. Results: Of 5709 de-duplicated records, 148 were included in the narrative synthesis. The majority of studies ( n = 102, 68.9 per cent) reported measures of survival and/or recurrence; approximately three-quarters ( n = 75, 73.5 per cent) had less than 5 years follow-up. Aesthetic outcome was reported in half of studies ( n = 75, 50.7 per cent) using mainly subjective, non-validated measurement tools. The time point at which aesthetic assessment was conducted was highly variable, and only defined in 48 (64.0 per cent) studies and none included a preoperative baseline for comparison. Few studies reported quality of life ( n = 30, 20.3 per cent), functional outcomes ( n = 5, 3.4 per cent) or resource use ( n = 28, 18.9 per cent). Conclusion: Given the oncological equivalence of TM and mastectomy, treatment decisions are often driven by aesthetic and functional outcomes, which are infrequently and inconsistently reported with non-validated measurement tools. Abstract : Given the oncological equivalence of therapeutic mammaplasty and mastectomy, treatment decisions are often driven by aesthetic and functional outcomes, which should have a robust evidence base. However, this review has shown such outcomes are infrequently and inconsistently reported with non-validated measurement tools. A core outcome set will enable standardization of reporting and synthesis of high-quality evidence to guide clinical decision-making and patient selection.